Pretty little liars - Shepard, Sara, 1977- (New York, NY : HarperTempest, 2006)
When one of their tightly-knit group mysteriously disappears, four high school girls find their friendship difficult to maintain when they begin receiving taunting messages from someone who seems to know everything about their past and present secrets.
Keywords: Missing persons -- Juvenile fiction; Friendship -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Juvenile fiction; High schools -- Juvenile fiction; Mystery fiction